Physical profiling of international cricket players: an investigation between bowlers and batters - Weldon, Anthony; Clarke, Neil; Pote, Lee; Bishop, Chris (Biology of Sport, 2021)
This study aimed to develop a physical profile of international cricketers, and investigate if positional differences exist between bowlers and batters. Nineteen, international male cricketers, eleven bowlers (age 24.1 ± 5.2 years; height 179.73 ± 5.27 cm; weight 73.64 ± 6.65 kg), and eight batters (age 22.9 ± 3.8 years; height 180.25 ± 5.57 cm; weight 77.01 ± 8.99 kg) participated in this study. The physical test battery included; power, speed, strength and aerobic fitness tests. Batters demonstrated significantly higher scores for the countermovement jump (p < 0.03; ES = -1.55) and squat jump (p < 0.03; ES = -0.98). Furthermore, batters showed non-significant but small ES for faster 0–5 m (ES = 0.40) and 0–10 m (ES = 0.35) sprint times, superior hand grip strength (ES = -0.20), and higher Yo-Yo intermittent recovery test scores (ES = -0.46). Bowlers showed non-significant but small ES for faster 5 km time trials (ES = -0.51), lower bodyweight (ES = -0.42) and lower body fat percentage (ES = -0.30). However, intra-positional (i.e., seam and spin bowlers) and individual differences amongst players were observed. The physical profiles presented in this study can be used by coaches responsible for the physical development of cricket players to compare their existing data with. Furthermore, it is recommended that practitioners account for individual physical fitness profiles in addition to team profiles, to effectively design and evaluate tailored programs, with the aim of improving both physical and cricket performance.